Active Labor Market Policy in Austria: Practice and Evaluation Results - Helmut Hofer; Andrea Weber (Vierteljahrshefte zur Wirtschaftsforschung, 2006)
The importance of active labor market policy (ALMP) has been rising over the last 10 years in Austria, with public expenditures now amounting to about 0.6% of GDP. This paper provides a comprehensive overview of active labor market policies in Austria. We study the development of policy strategies in terms of the offered program mix and public expenditures for labor market policy over time. We also present existing evidence on ALMP effectiveness by discussing the focus and results of the main Austrian evaluation studies. – – Die Bedeutung der aktiven Arbeitsmarktpolitik hat in Österreich in den letzten 10 Jahren zugenommen. Deren Ausgaben machen aktuell 0,6% des BIP aus. Dieser Beitrag bietet einen kompakten Überblick über diese Maßnahmen. Untersucht werden die Politikstrategien im Hinblick auf die Zusammensetzung der Programme und deren Kosten im Zeitablauf. Die Wirkungen der aktiven Arbeitsmarktpolitik werden anhand der wesentlichen Evaluierungsstudien für Österreich diskutiert.
Keywords: 330; Arbeitsmarktpolitik; Wirkungsanalyse; Österreich